The incidence and prevalence of systemic lupus erythematosus in the UK, 1999–2012 - Rees, Frances; Doherty, Michael; Grainge, Matthew J.; Davenport, Graham; Lanyon, Peter; Zhang, Weiya (BMJ Publishing Group, 2014)
Objectives: To estimate the incidence and prevalence of systemic lupus erythematosus (SLE) in the UK over the period 1999–2012.